Referenciação em fórum digital: uma contribuição para o ensino de língua portuguesa - Pinelli, Danielle Maximo Plens (2009)
This paper aims to present an analysis of the discourse reference in digital forums, especially concerning to the role of indirect anaphors in the discursive topic development. This way, we will bring together studies about the hypertextual writing (Xavier, 2002; Crystal, 2001; Marcuschi, 2004; Espéret, 1996 and Komesu, 2005), and studies about the discourse reference, concept understood as an activity by which the subjects, as partners in the interaction, build and re-build, in and by the discourse, the objects they want to refer to (cf.: Mondada and Dubois, 2003; Koch, 2004, 2005 and 2008; Marcuschi, 2001, 2005, 2006 and 2007). Among the discourse reference studies, it s relevant to mention here the phenomenon named indirect anaphors as the way it s understood by Schwarz (2000) and Marcuschi (2005). Owing to the objective of this research, we selected a digital forum, set on the worldwide web and, from this forum, we extracted messages produced by users during the discussion of a specific discursive topic. The results of the analysis show that in the course of the interaction, the inter-actors build anaphors with no previous referent that is able to be pointed out in the text, because they are merely suggested in the discursive memory or in the co-text, using words or expressions that work as their anchors . Nonetheless, these anaphors, far from compromising the interacting, they remark the fundamental multi-linearity of a given text and contribute to the textual progression and the global coherence